An open-label randomised controlled trial on the efficacy of adding intranasal fentanyl to intravenous tramadol in patients with moderate to severe pain following acute musculoskeletal injuries. - Chew, Keng Sheng; Shaharudin, Abdul Hafiz (Singapore Medical Journal, 2017)
INTRODUCTION